Pendekatan rasional terapi infeksi saluran kemih pada USILA (usia lanjut) - I Gde Raka Widiana, I Gde Raka Widiana (Universitas Gadjah Mada, 1996)
Aging may affect functional and structural changes of the urinary tract which modify the response against infection. Sructural changes in elderly such as prostate hypertrophy, urinary tract stone, the use of catheter, and the presence of cystoceles should be treated properly. Attention should be paid on functional abnormalities in elderly including bladder atonia, neurologic defects, and prolonged bed rest. Inadequate immune response in elderly may also play a role in the changes. Those factors make the treatment of urinary tract infections in elderly have to be carried out more radically.Complicated urinary tract infections, infection in males with prostate hypertrophy, and pyelonephritis need prolonged treatment. Recurrent urinary tract infections in female elderly patients need early prophylactic treatment. Doing a culture of the causative microorganisms and a sensitivity test for the appropriate antibiotics should be taken into consideration in the selection of the antibiotics. Flouroquinolones and cephalosporins seem to be drugs of choice in multiresistant and severe casesKey words: urinary tract infections - elderly - functional changes - structural changes - treatment